Interpretation: experience of place - Schooler, Luke A. (Kansas State University, 2009)
The site for the Riverpond Visitor Center is located three miles northeast of Manhattan, Kansas, along K-13 on the eastern end of Riverpond Park. The design of the visitor center addresses four problems: 1) the fact that many families prefer to stay inside their homes rather than experience the outdoors, based on a study done by the Center on Education Policy in 2008, 2) people are uninformed about sustainable design practices and sustainable energies 3) people lack experience and knowledge of the natural environment creating a preference for the visual characteristics of non-native plant species, and 4) interpretive centers that attempt to reconnect people and the landscape use prescriptive interpretive methods that distract the visitor from the interpretive process. To better understand the relationship of people and the landscape, research was conducted to address the problems stated above. Two articles were reviewed that describe the importance of drawing attention to beauty in the landscape. Two precedent studies were conducted on built projects that use native plant species and vernacular architecture. The program for the visitor center was based on the project research and informed the site inventory and analysis. The site inventory and analysis of existing site conditions creates a strong foundation from which to design the visitor center. The project then went into schematic design and design development. The design of the Riverpond Visitor Center connects people to the landscape by directing them through the native tall grass prairie, informs visitors about stormwater management, wind and solar energy through demonstration, is designed using native prairie species and native limestone, and focuses visitors’ experience on the tall grass prairie by fading the line between architecture and landscape.
Keywords: Visitor center; Interpretation; Green roof; Earth shelter; Native plants; Vernacular architecture; Landscape Architecture (0390)